2016
DOI: 10.1080/14739879.2016.1175913
|View full text |Cite
|
Sign up to set email alerts
|

Do quality indicators for general practice teaching practices predict good outcomes for students?

Abstract: (200 words)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(26 reference statements)
1
1
0
1
Order By: Relevance
“…They have shown no evidence of academic disadvantage to students placed in a relatively isolated rural campus and in smaller practices, which may have been perceived to struggle to provide sufficient clinical exposure. They reinforce previous work at Keele University, which showed that learning in rural practices has no predictive value for students' satisfaction with their placements 20 . Finally, these data are important nationally; in England, 9.5 million people (19.3% of the population) 2 live in rural areas where there are isolated pockets of intense social deprivation, with specific health issues such as reduced access to health professionals and services, and a reluctance to seek help 21 .The Department of Health aims for 50% of medical graduates to enter general practice 22,23 and recruitment to rural practices has recently been described as being at 'crisis point' 24 .…”
Section: Discussionsupporting
confidence: 86%
“…They have shown no evidence of academic disadvantage to students placed in a relatively isolated rural campus and in smaller practices, which may have been perceived to struggle to provide sufficient clinical exposure. They reinforce previous work at Keele University, which showed that learning in rural practices has no predictive value for students' satisfaction with their placements 20 . Finally, these data are important nationally; in England, 9.5 million people (19.3% of the population) 2 live in rural areas where there are isolated pockets of intense social deprivation, with specific health issues such as reduced access to health professionals and services, and a reluctance to seek help 21 .The Department of Health aims for 50% of medical graduates to enter general practice 22,23 and recruitment to rural practices has recently been described as being at 'crisis point' 24 .…”
Section: Discussionsupporting
confidence: 86%
“…Desta forma, como a EPS é vista pelos profissionais precisa ser incluída na avaliação. Na tentativa de medir a qualidade, pode ser frágil considerar os fatores de avaliação formativa individualizada, mas o dado numérico em sua amplitude pode auxiliar na avaliação geral e na proposição de alterações de novas atividades com a mesma temática (11) . Nesse sentido, os indicadores do serviço da EPS emergem, principalmente, da capacidade de planejamento das atividades.…”
Section: Análise De Indicadores Relacionados Ao Profissionalunclassified
“…Some do these things even though they believe them to be ‘unethical and deserving of punishment’, which demonstrates how important the feedback is perceived to be. Interestingly, researchers have generally failed to demonstrate a clear relationship between students’ evaluations and educational outcomes or the educational value of what teachers do to attempt to influence the feedback …”
mentioning
confidence: 99%